Synergistic effect between 1D Co3S4/MoS2 heterostructures to boost the performance for alkaline overall water splitting. Issue 10 (29th March 2022) - Li, Zilong; Xu, Weilong; Yu, Xiaolong; Yang, Sanxi; Zhou, Yang; Zhou, Kai; Wu, Qikai; Ning, Shunlian; Luo, Mi; Zhao, Dengke; Wang, Nan
Abstract : Reasonable design and construction of hetero-bimetal sulfides with high performance for the oxygen/hydrogen evolution reaction (O/HER) in an alkaline electrolyte are promising but still challenging. Abstract : The reasonable design and construction of hetero-bimetal sulfides with high performance for the oxygen/hydrogen evolution reaction (O/HER) in an alkaline electrolyte are promising but still challenging. Herein, 1D Co3 S4 /MoS2 bimetallic sulfide nanorods (Co3 S4 /MoS2 NRs) were prepared using MoO3 nanorods and ZIF-67 as the precursors. As-prepared Co3 S4 /MoS2 NRs showed excellent HER and OER activity, including low overpotentials at 10 mA cm −2 (116 and 280 mV) and Tafel slopes (59 and 52 mV dec −1 ). Furthermore, the density functional theory (DFT) reveals that the introduction of Co3 S4 is conducive to reducing H2 O dissociation during the HER process. In addition, Co3 S4 also can effectively regulate the d orbital electrons of Mo in MoS2, which is beneficial for optimizing the H adsorption energy, thus enhancing the HER performance. Benefitting from excellent OER and HER activities, the Co3 S4 /MoS2 NR based-electrolyzer for overall water spitting exhibits a low cell voltage of 1.66 V to reach 20 mA cm −2 along with good stability.